Maintenance management process model for school buildings: an application of IDEF0 modelling methodology - Akasah, Zainal Abidin; Amirudin, Roslan (Taylor and Francis Publisher, 2015)
The lack of a clear understanding of the maintenance management process is one of the major sources of difficulties in the maintenance of school buildings. A clearer understanding of the maintenance management process can be achieved by constructing a process model of the existing practices using a suitable process modelling technique. The purpose of this study was to develop a process model for the management of maintenance of school buildings using the IDEF0 structured modelling technique. The modelling process is divided into three phases, (i) the information gathering phase, (ii) the model development phase and (ii) the experts' evaluation and validation phase. In the first phase, information on existing maintenance practices was obtained through questionnaires and document analysis of policies, standing orders and maintenance reports. In the second phase, a process model was drafted through an iterative process using the IDEF0 process modelling technique. In the third phase, the draft process model was submitted to three experts on maintenance management from the Ministry of Education Malaysia for evaluation and validation. A ready to implement process model for the maintenance management of school buildings was constructed upon validation by the experts.